Sweden Feminist Foreign Policy in Building Women Entrepreneurship (SHE-Leads Program) in Saudi Arabia 2017-2021 - Bhilla Aliffitria; Yanyan M Yani; Dina Yulianti (Yayasan Ilomata, 2023)
In 2017, Sweden built women entrepreneurship (SHE-Leads Program) in Saudi Arabia to foster networks, meetings, and educational opportunities to train Saudi Arabian women as entrepreneurs and innovators. The aim of this study is to elucidate how did Sweden’s feminist foreign policy build women’s entrepreneurship in Saudi Arabia 2017-2021. This study was conducted using interview method by electronic mail with Monika Wirkkala, Director of the Department of Communication and Analysis of Sweden at the Swedish Institute (SI). The data are analyzed using the feminist foreign policy concept proposed by Cheung, Gürsel, Kirchner, & Scheyer, which encompasses five core values of feminist foreign policy. The results were as follows: (1) intersectionality, Sweden applied this policy fairly without any differentiation among participants; (2) empathetic reflectivity, Swedish leaders and stakeholders responded positively to this policy by developing SHE-Pioneer; (3) substantive representation and participation, Sweden actively engaged women from the Swedish Institute (SI) and collaborated with non-state actors in formulating and implementing policies; (4) accountability, the policy incorporates evaluation and monitoring, involving program participants, stakeholders, and partners; (5) commitment to peace, the SHE-Leads Program policy is implemented through collaboration, involving participants from diverse backgrounds, and aims to strengthen relations between Sweden and Saudi Arabia. This study concluded that Sweden feminist foreign policy in building women entrepreneurship in Saudi Arabia (SHE-Leads Program) has reflected Sweden feminist foreign policy and has implemented the five core values of the feminist foreign policy concept.